Coffee intake, caffeine metabolism genotype, and survival among men with prostate cancer - Gregg, Justin R.; Kim, Jeri; Logothetis, Christopher; Hanash, Sam; Zhang, Xiaotao; Manyam, Ganiraju; Muir, Kenneth; Giles, Graham G.; Stanford, Janet L.; Berndt, Sonja I.; Kogevinas, Manolis; Brenner, Hermann; et al. (European urology oncology, 2022)
Background - Coffee intake may lower prostate cancer risk and progression, but postdiagnosis outcomes by caffeine metabolism genotype are not well characterized. - Objective - To evaluate associations between coffee intake, caffeine metabolism genotype, and survival in a large, multicenter study of men with prostate cancer. - Design, setting, and participants - Data from The PRACTICAL Consortium database for 5727 men with prostate cancer from seven US, Australian, and European studies were included. The cases included had data available for the CYP1A2 −163C>A rs762551 single-nucleotide variant associated with caffeine metabolism, coffee intake, and >6 mo of follow-up. - Outcome measurements and statistical analysis - Multivariable-adjusted Cox proportional hazards models across pooled patient-level data were used to compare the effect of coffee intake (categorized as low [reference], high, or none/very low) in relation to overall survival (OS) and prostate cancer-specific survival (PCSS), with stratified analyses conducted by clinical disease risk and genotype. - Results and limitations - High coffee intake appeared to be associated with longer PCSS (hazard ratio [HR] 0.85, 95% confidence interval [CI] 0.68-1.08; p = 0.18) and OS (HR 0.90, 95% CI 0.77-1.07; p = 0.24), although results were not statistically significant. In the group with clinically localized disease, high coffee intake was associated with longer PCSS (HR 0.66, 95% CI 0.44-0.98; p = 0.040), with comparable results for the group with advanced disease (HR 0.92, 95% CI 0.69-1.23; p = 0.6). High coffee intake was associated with longer PCSS among men with the CYP1A2 AA (HR 0.67, 95% CI 0.49-0.93; p = 0.017) but not the AC/CC genotype (p = 0.8); an interaction was detected (p = 0.042). No associations with OS were observed in subgroup analyses (p > 0.05). Limitations include the nominal statistical significance and residual confounding. - Conclusions - Coffee intake was associated with longer PCSS among men with a CYP1A2 −163AA (*1F/*1F) genotype, a finding that will require further replication. - Patient summary - It is likely that coffee intake is associated with longer prostate cancer-specific survival in certain groups, but more research is needed to fully understand which men may benefit and why.
Online veröffentlicht: 20. August 2022, Version der Publikation: 14. Juni 2023
Gesehen am 12.12.2023